СОВРЕМЕННОЕ СОСТОЯНИЕ И ТЕНДЕНЦИИ РАЗВИТИЯ В КОНТЕКСТЕ КОМПЕТЕНТНОСТНОГО ПОДХОДА - Альджанова, Г.А. (SCIENCE and SOCIETY, 2018)
The article deals with modern approaches in investigating the problems of developing professional competence in future pedagogues, identifying its role in the cultural system and in the upbringing of future teachers, in particular and determining the general characteristics. Nowadays there are many investigations on the given topic, focused on the study of such phenomena as «pedagogical competence».